2020
DOI: 10.9734/jsrr/2020/v26i330232
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Market Potentials and Utilization of Cashew Fruit: Perspectives of Cashew Farmers in the Brong Ahafo Region of Ghana

Abstract: In spite of its nutritional and economic values, Cashew apple has received low patronage in terms of commercialization and utilization and policy focus. This has led to underutilization and wastage of fresh fruits, which could contribute to farmer’s income. This study explored the state of awareness of the market potential and consumption of cashew apple among farm households in selected areas of Brong Ahafo in Ghana. A total 200 respondents were randomly interviewed in addition to a Focus group discussion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
5
5
0
Order By: Relevance
“…These results suggest the need to intensify educational or training programs on regular basis and also encourage well-educated ones to participate in cashew activities, in order to improve the value of the cashew industry in Ghana. The current observation is consistent with an earlier study undertaken by Ackah et al [ 10 ] in Ghana and that of Dimoso et al [ 15 ] in Tanzania who recorded that about 66.5% and 82%, respectively, of major cashew stakeholders (farmers) have no or basic education. Oluyole et al [ 11 ] also revealed that the Nigerian cashew industry has about 88.2% of its workforce having no or basic formal education.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These results suggest the need to intensify educational or training programs on regular basis and also encourage well-educated ones to participate in cashew activities, in order to improve the value of the cashew industry in Ghana. The current observation is consistent with an earlier study undertaken by Ackah et al [ 10 ] in Ghana and that of Dimoso et al [ 15 ] in Tanzania who recorded that about 66.5% and 82%, respectively, of major cashew stakeholders (farmers) have no or basic education. Oluyole et al [ 11 ] also revealed that the Nigerian cashew industry has about 88.2% of its workforce having no or basic formal education.…”
Section: Resultssupporting
confidence: 93%
“…Comparatively, the good amount of women involved in the cashew industry in the study regions is an added advantage in improving their standard of living, reducing poverty, and ensuring food and nutrition security and quality of cashew since women are known to be meticulous and loyal in their dealings [ 14 ]. Dimoso et al [ 15 ] and Ackah et al [ 10 ] identified the cashew industry as male-dominated (54.7-74.1%), with the majority being 30-60 years of age, which is in accordance with the findings of this present study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations